Gainsharing handbook. - Philippine Exporters Confederation ([Pasay City] Philippine Exporters Confederation, 1997)
The handbook aims to provide some guidelines in the development and implementation of a productivity gainsharing program as an integral part of the goal of improving the company's overall productivity.
Reprint of the same ed. published by Dept. of Labor and Employment, National Wages and Productivity Commission.
Keywords: Gain sharing -- Philippines -- Handbooks, manuals, etc